Preliminary Memorandum on Fourth Five-Year Plan Bihar - Planning Commission (Planning Commission, 1965)
The total outlay proposed in the Fourth Plan is Rs. 9.39.52 crores. Though full details in respect of all the sectors are not yet available, it is estimated that a sum of Rs. 103.58 crores would be needed in terms of foreign exchange for irrigation, power, industries and roads programmes. Similarly , the spill-over expenditure in respect of these sectors is estimated to be Rs. 155 crores. The experience in the past has been that delay in the allocation and release of foreign exchange had led to consequent delays in the implementation of schemes.
Bihar